Outcome of surgical parathyroidectomy for tertiary hyperparathyroidism in kidney transplant recipients: tertiary hyperparathyroidism should not be ignored, for the sake of precious allografts - Michio Nakamura; Shinya Takiguchi; Saeko Uehara; Yusuke Tomita (Renal Failure)
Tertiary hyperparathyroidism is a complication of kidney transplantation. This complicated condition carries over from the dialysis period and varies according to the function of the transplanted allograft. Treatments include pharmacotherapy (mainly using calcimimetics) and parathyroidectomy, but calcimimetics are currently not covered by the national insurance system in Japan. Two types of parathyroidectomy can be performed: subtotal parathyroidectomy; and total parathyroidectomy with partial autograft. Both types can be expected to improve hypercalcemia. Concerns about the postoperative deterioration of allograft function are influenced by preoperative allograft function, which is even more likely to be affected by early surgery after kidney transplantation. In general, transient deterioration of allograft function after surgery is not expected to affect graft survival rate in the medium to long term. Tertiary hyperparathyroidism in kidney transplant recipients negatively impacts allograft and patient survival rates, and parathyroidectomy can be expected to improve prognosis in both kidney recipients and dialysis patients. However, studies offering high levels of evidence remain lacking.